KEDUDUKAN, TUGAS DAN FUNGSI PENYIDIK PEGAWAI NEGERI SIPIL DI ACEH - Andriansyah, Mahdi Syahbandir, Adwani. (Jurnal Ilmu Hukum, 2015)
Abstract : Law Number 11 Year 2006 concerning Aceh Government Article 133 states that the task of inquiry and investigation to the enforcement of Islamic law under the authority of the Syar'iyah Court along the jinayah was conducted by the Indonesian National Police and Civil Servant Investigators. Therefore, Qanun Aceh Number 12 Year 2012 concerning the Civil Servant Investigators was established. Article 1 number 11 the investigators Qanun mentioned that official Civil Servant Investigators abbreviated to PPNS are certain Civil Servant investigators which are defined in the KUHAP (Criminal Code). The aims of this research were to examine the position, duties and functions of PPNS in Aceh, the implementation of duties and functions of PPNS in Aceh, and the inhibiting factors of the duties and functions implementation of PPNS in Aceh. Normative legal research method was used. The results showed that firstly, PPNS in Aceh was resident and responsible to the Governor/Regent/Mayor, run the function as enforcers of local regulations/Aceh Qanun and other legislations in Aceh. Secondly, the implementation of the duties and functions was not fully guided on PPNS Qanun. Thirdly, the main inhibiting factor of duties and functions implementation of PPNS in Aceh was regulation, had no standard operational procedure as guidance of duties implementation of PPNS in Aceh, as well as the internal and external factors. Therefore, it was suggested that the Government of Aceh and District/City must have a high commitment in supporting the duties and functions of PPNS.Keywords: Civil Servant Investigator and Local Regulation Number 12 Year 2012. Abstrak: Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh pasal 133 menyebutkan bahwa tugas penyelidikan dan penyidikan untuk penegakan syariat Islam yang menjadi kewenangan Mahkamah Syar’iyah sepanjang mengenai jinayah dilakukan oleh Kepolisian Negara Republik Indonesia dan Penyidik Pegawai Negeri Sipil. Atas dasar tersebut dibentuk Qanun Aceh Nomor 12 Tahun 2012 tentang Penyidik Pegawai Negeri Sipil. Pasal 1 angka 11 Qanun PPNS menyebutkan bahwa Pejabat Penyidik Pegawai Negeri Sipil yang selanjutnya disingkat PPNS adalah Pegawai Negeri Sipil tertentu sebagaimana dimaksud dalam KUHAP. Penelitian ini bertujuan untuk mengetahui dan menjelaskan tentang kedudukan, tugas dan fungsi PPNS di Aceh; mengetahui dan menjelaskan implementasi pelaksanaan tugas dan fungsi PPNS di Aceh; dan mengetahui serta menjelaskan faktor penghambat pelaksanaan tugas dan fungsi PPNS di Aceh. Metode penelitian yang digunakan adalah metode penelitian hukum normatif. Hasil penelitian menunjukkan bahwa: pertama, PPNS di Aceh berkedudukan dan bertanggung jawab kepada Gubernur/Bupati/Walikota, menjalankan fungsi sebagai aparat penegak peraturan daerah/Qanun Aceh dan peraturan perundang-undangan lainnya di Aceh. Kedua, implementasi pelaksanaan tugas dan fungsi PPNS di Aceh belum sepenuhnya berpedoman pada Qanun PPNS. Ketiga, faktor utama penghambat pelaksanaan tugas dan fungsi PPNS di Aceh adalah regulasi, belum ada SOP sebagai petunjuk pelaksanaan tugas PPNS di Aceh, faktor internal dan eksternal. Disarankan kepada Pemerintah Aceh dan Pemerintah Kabupaten/Kota harus memiliki komitmen yang tinggi dalam mendukung tugas pokok dan fungsi PPNS.Kata kunci : Penyidik Pegawai Negeri Sipil dan Qanun Nomor 12 tahun 2012.